Saruplase is a safe and effective thrombolytic agent, observations in 1698 patients: results of the PASS study - Vermeer, Frank; Bösl, I.; Meyer, J.; Bär, F.; Charbonnier, B.; Windeler, Jürgen; Barth, H. (Journal of thrombosis and thrombolysis, 1999)
Saruplase (unglycosylated human-type high molecular weight single-chain urokinase-type plasminogen activator) was given to 1698 patients in the open-label Practical Applicability of Saruplase Study (PASS), which assessed the safety and efficacy of saruplase in the treatment of acute myocardial infarction. Thirty-seven hospitals in Europe participated in the study. All patients received 20 mg saruplase as a bolus followed by an infusion of 60 mg saruplase over 1 hour. Prior to the infusion of saruplase, 62% of the patients received a bolus of 5000 U of heparin, and after saruplase a 24-hour intravenous infusion of heparin was given to 95% of patients. The mean age of the patients was 59 years and 80.1% were male. The median delay from the onset of chest pain to the start of saruplase infusion was 145 minutes. Acute angiography was performed in 8 of the participating 37 centers in 350 patients (20.6%), on average 85 minutes (median) after the start of the saruplase infusion. TIMI 3 flow was obtained in 186 patients (53.1%) and TIMI 2 flow in 61 patients (17.4%). Patency rates were similar for patients with anterior and inferior infarction. ECG signs suggestive of reperfusion were seen in 63% of the patients. In-hospital mortality was low (92 patients; 5.4%), and nonfatal recurrent myocardial infarction was seen in 60 patients (3.5%). Severe bleeding complications occurred in 92 patients (5.4%), 21 of whom (1.2%) needed a blood transfusion. An intracerebral hemorrhage was observed in eight patients (0.5%), and seven patients (0.4%) suffered from a thromboembolic stroke. At discharge 85.9% of the patients were in NYHA functional class I. One-year mortality was low (142 patients; 8.4%). Mortality was high in patients with TIMI 0 or 1 flow at the acute angiography who did not undergo rescue PTCA (9/39; 23.1%), lower in patients with TIMI 0 or 1 flow followed by successful rescue PTCA (7/64; 10.9%), and low in patients with TIMI 2 flow (1/61; 1.6%) or with TIMI 3 flow (2/186; 1.1%). Patency rates and (bleeding) complications did not differ between patients with a body weight greater than or less than 70 kilograms. No antibodies against saruplase were detected in samples from 455 patients. In conclusion, it can be stated that saruplase, given in combination with aspirin and intravenous heparin, can be given safely and effectively to patients with acute myocardial infarction.